Liver sinusoidal endothelial cells induce immunosuppressive IL‐10‐producing Th1 cells via the Notch pathway. Issue 7 (12th May 2015) - Neumann, Katrin; Rudolph, Christine; Neumann, Christian; Janke, Marko; Amsen, Derk; Scheffold, Alexander
<x xml:space="preserve">Abstract</x> Under homeostasis, liver sinusoidal endothelial cells (LSECs) shift intrahepatic T‐cell responses towards tolerance. However, the role of LSECs in the regulation of T‐cell‐induced liver inflammation is less clear. Here, we studied the capacity of LSECs to modulate pro‐inflammatory Th1‐cell differentiation in mice. Using in vitro co‐culture systems and subsequent cytokine analysis, we showed that LSECs induced high amounts of the anti‐inflammatory cytokine IL‐10 in developing Th1 cells. These LSEC‐stimulated Th1 cells had no pro‐inflammatory capacity in vivo but instead actively suppressed an inflammatory Th1‐cell‐induced delayed‐type hypersensitivity reaction. Blockage of IL‐10 signaling in vivo inhibited immunosuppressive activity of LSEC‐stimulated Th1 cells. We identified the Notch pathway as a mechanism how LSECs trigger IL‐10 expression in Th1 cells. LSECs expressed high levels of the Delta‐like and Jagged family of Notch ligands and induced expression of the Notch target genes hes‐1 and deltex‐1 in Th1 cells. Blockade of Notch signaling selectively inhibited IL‐10 induction in Th1 cells by LSECs. Our findings suggest that LSEC‐induced IL‐10 expression in Th1 cells via the Notch pathway may contribute to the control of hepatic inflammatory immune responses by induction of a self‐regulatory mechanism in pro‐inflammatory Th1 cells.